The commodity futures market guide - Kroll, Stanley; Shishko, Irwin (New York : Harper & Row, 1973)
This book evaluates the methods presently used to guide individuals in commodity trading. It is divided into 6 parts: organised commodity markets-their development and operation; the regulation of commodity markets; futures as a pricing medium; commodity price analysis; speculative trading; the use of futures markets by commercial interests.
Includes bibliographical references (p. 355-357) and index.
lje 22/1/19
Loans
Keywords: Commodity exchanges; Futures trading